Evaluating the possible impact of pension reforms on elderly poverty in Europe - Grech, Aaron George (Munich, 2014)
"Since the 1990s reforms have changed substantially both the nature of state pension provision and the level of generosity. This article tries to assess the impact of these changes using estimates of pension wealth for a number of hypothetical cases. By focusing on all prospective pension transfers rather than just those at the point of retirement, this approach can provide additional insights, especially on the impact of changes in benefit indexation. These estimates corroborate existing evidence that reforms have decreased generosity significantly. Moves to link benefits to contributions have made systems less progressive, raising adequacy concerns for certain groups. The reforms have, in particular, strengthened the need of ensuring better access to labour markets, of having in place adequate crediting arrangements and minimum pensions."